5. Let
. Note that we want this variable change to be reversible, so we tacitly assume 0 ≤ θ ≤ π/2. Then
![\cos(\theta) = \sqrt{1 - \sin^2(\theta)} = \sqrt{1 - x^2}](https://tex.z-dn.net/?f=%5Ccos%28%5Ctheta%29%20%3D%20%5Csqrt%7B1%20-%20%5Csin%5E2%28%5Ctheta%29%7D%20%3D%20%5Csqrt%7B1%20-%20x%5E2%7D)
and
. So the integral transforms to
![\displaystyle \int \frac{x^3}{\sqrt{1-x^2}} \, dx = \int \frac{\sin^3(\theta)}{\cos(\theta)} \cos(\theta) \, d\theta = \int \sin^3(\theta) \, d\theta](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cint%20%5Cfrac%7Bx%5E3%7D%7B%5Csqrt%7B1-x%5E2%7D%7D%20%5C%2C%20dx%20%3D%20%5Cint%20%5Cfrac%7B%5Csin%5E3%28%5Ctheta%29%7D%7B%5Ccos%28%5Ctheta%29%7D%20%5Ccos%28%5Ctheta%29%20%5C%2C%20d%5Ctheta%20%3D%20%5Cint%20%5Csin%5E3%28%5Ctheta%29%20%5C%2C%20d%5Ctheta)
Reduce the power by writing
![\sin^3(\theta) = \sin(\theta) \sin^2(\theta) = \sin(\theta) (1 - \cos^2(\theta))](https://tex.z-dn.net/?f=%5Csin%5E3%28%5Ctheta%29%20%3D%20%5Csin%28%5Ctheta%29%20%5Csin%5E2%28%5Ctheta%29%20%3D%20%5Csin%28%5Ctheta%29%20%281%20-%20%5Ccos%5E2%28%5Ctheta%29%29)
Now let
, so that
. Then
![\displaystyle \int \sin(\theta) (1-\cos^2(\theta)) \, d\theta = - \int (1-y^2) \, dy = -y + \frac13 y^3 + C](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cint%20%5Csin%28%5Ctheta%29%20%281-%5Ccos%5E2%28%5Ctheta%29%29%20%5C%2C%20d%5Ctheta%20%3D%20-%20%5Cint%20%281-y%5E2%29%20%5C%2C%20dy%20%3D%20-y%20%2B%20%5Cfrac13%20y%5E3%20%2B%20C)
Replace the variable to get the antiderivative back in terms of x and we have
![\displaystyle \int \frac{x^3}{\sqrt{1-x^2}} \, dx = -\cos(\theta) + \frac13 \cos^3(\theta) + C](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cint%20%5Cfrac%7Bx%5E3%7D%7B%5Csqrt%7B1-x%5E2%7D%7D%20%5C%2C%20dx%20%3D%20-%5Ccos%28%5Ctheta%29%20%2B%20%5Cfrac13%20%5Ccos%5E3%28%5Ctheta%29%20%2B%20C)
![\displaystyle \int \frac{x^3}{\sqrt{1-x^2}} \, dx = -\sqrt{1-x^2} + \frac13 \left(\sqrt{1-x^2}\right)^3 + C](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cint%20%5Cfrac%7Bx%5E3%7D%7B%5Csqrt%7B1-x%5E2%7D%7D%20%5C%2C%20dx%20%3D%20-%5Csqrt%7B1-x%5E2%7D%20%2B%20%5Cfrac13%20%5Cleft%28%5Csqrt%7B1-x%5E2%7D%5Cright%29%5E3%20%2B%20C)
![\displaystyle \int \frac{x^3}{\sqrt{1-x^2}} \, dx = -\frac13 \sqrt{1-x^2} \left(3 - \left(\sqrt{1-x^2}\right)^2\right) + C](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cint%20%5Cfrac%7Bx%5E3%7D%7B%5Csqrt%7B1-x%5E2%7D%7D%20%5C%2C%20dx%20%3D%20-%5Cfrac13%20%5Csqrt%7B1-x%5E2%7D%20%5Cleft%283%20-%20%5Cleft%28%5Csqrt%7B1-x%5E2%7D%5Cright%29%5E2%5Cright%29%20%2B%20C)
![\displaystyle \int \frac{x^3}{\sqrt{1-x^2}} \, dx = \boxed{-\frac13 \sqrt{1-x^2} (2+x^2) + C}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cint%20%5Cfrac%7Bx%5E3%7D%7B%5Csqrt%7B1-x%5E2%7D%7D%20%5C%2C%20dx%20%3D%20%5Cboxed%7B-%5Cfrac13%20%5Csqrt%7B1-x%5E2%7D%20%282%2Bx%5E2%29%20%2B%20C%7D)
6. Let
and
. It follows that
![\cos(\theta) = \dfrac1{\sec(\theta)} = \dfrac1{\sqrt{1+\tan^2(\theta)}} = \dfrac3{\sqrt{9+x^2}}](https://tex.z-dn.net/?f=%5Ccos%28%5Ctheta%29%20%3D%20%5Cdfrac1%7B%5Csec%28%5Ctheta%29%7D%20%3D%20%5Cdfrac1%7B%5Csqrt%7B1%2B%5Ctan%5E2%28%5Ctheta%29%7D%7D%20%3D%20%5Cdfrac3%7B%5Csqrt%7B9%2Bx%5E2%7D%7D)
since, like in the previous integral, under this reversible variable change we assume -π/2 < θ < π/2. Over this interval, sec(θ) is positive.
Now,
![\displaystyle \int \frac{x^3}{\sqrt{9+x^2}} \, dx = \int \frac{27\tan^3(\theta)}{\sqrt{9+9\tan^2(\theta)}} 3\sec^2(\theta) \, d\theta = 27 \int \frac{\tan^3(\theta) \sec^2(\theta)}{\sqrt{1+\tan^2(\theta)}} \, d\theta](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cint%20%5Cfrac%7Bx%5E3%7D%7B%5Csqrt%7B9%2Bx%5E2%7D%7D%20%5C%2C%20dx%20%3D%20%5Cint%20%5Cfrac%7B27%5Ctan%5E3%28%5Ctheta%29%7D%7B%5Csqrt%7B9%2B9%5Ctan%5E2%28%5Ctheta%29%7D%7D%203%5Csec%5E2%28%5Ctheta%29%20%5C%2C%20d%5Ctheta%20%3D%2027%20%5Cint%20%5Cfrac%7B%5Ctan%5E3%28%5Ctheta%29%20%5Csec%5E2%28%5Ctheta%29%7D%7B%5Csqrt%7B1%2B%5Ctan%5E2%28%5Ctheta%29%7D%7D%20%5C%2C%20d%5Ctheta)
The denominator reduces to
![\sqrt{1+\tan^2(\theta)} = \sqrt{\sec^2(\theta)} = |\sec(\theta)| = \sec(\theta)](https://tex.z-dn.net/?f=%5Csqrt%7B1%2B%5Ctan%5E2%28%5Ctheta%29%7D%20%3D%20%5Csqrt%7B%5Csec%5E2%28%5Ctheta%29%7D%20%3D%20%7C%5Csec%28%5Ctheta%29%7C%20%3D%20%5Csec%28%5Ctheta%29)
and so
![\displaystyle 27 \int \tan^3(\theta) \sec(\theta) \, d\theta = 27 \int \frac{\sin^3(\theta)}{\cos^4(\theta)} \, d\theta](https://tex.z-dn.net/?f=%5Cdisplaystyle%2027%20%5Cint%20%5Ctan%5E3%28%5Ctheta%29%20%5Csec%28%5Ctheta%29%20%5C%2C%20d%5Ctheta%20%3D%2027%20%5Cint%20%5Cfrac%7B%5Csin%5E3%28%5Ctheta%29%7D%7B%5Ccos%5E4%28%5Ctheta%29%7D%20%5C%2C%20d%5Ctheta)
Rewrite sin³(θ) just like before,
![\displaystyle 27 \int \frac{\sin(\theta) (1-\cos^2(\theta))}{\cos^4(\theta)} \, d\theta](https://tex.z-dn.net/?f=%5Cdisplaystyle%2027%20%5Cint%20%5Cfrac%7B%5Csin%28%5Ctheta%29%20%281-%5Ccos%5E2%28%5Ctheta%29%29%7D%7B%5Ccos%5E4%28%5Ctheta%29%7D%20%5C%2C%20d%5Ctheta)
and substitute
again to get
![\displaystyle -27 \int \frac{1-y^2}{y^4} \, dy = 27 \int \left(\frac1{y^2} - \frac1{y^4}\right) \, dy = 27 \left(\frac1{3y^3} - \frac1y\right) + C](https://tex.z-dn.net/?f=%5Cdisplaystyle%20-27%20%5Cint%20%5Cfrac%7B1-y%5E2%7D%7By%5E4%7D%20%5C%2C%20dy%20%3D%2027%20%5Cint%20%5Cleft%28%5Cfrac1%7By%5E2%7D%20-%20%5Cfrac1%7By%5E4%7D%5Cright%29%20%5C%2C%20dy%20%3D%2027%20%5Cleft%28%5Cfrac1%7B3y%5E3%7D%20-%20%5Cfrac1y%5Cright%29%20%2B%20C)
Put everything back in terms of x :
![\displaystyle \int \frac{x^3}{\sqrt{9+x^2}} \, dx = 9 \left(\frac1{\cos^3(\theta)} - \frac3{\cos(\theta)}\right) + C](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cint%20%5Cfrac%7Bx%5E3%7D%7B%5Csqrt%7B9%2Bx%5E2%7D%7D%20%5C%2C%20dx%20%3D%209%20%5Cleft%28%5Cfrac1%7B%5Ccos%5E3%28%5Ctheta%29%7D%20-%20%5Cfrac3%7B%5Ccos%28%5Ctheta%29%7D%5Cright%29%20%2B%20C)
![\displaystyle \int \frac{x^3}{\sqrt{9+x^2}} \, dx = 9 \left(\frac{\left(\sqrt{9+x^2}\right)^3}{27} - \sqrt{9+x^2}\right) + C](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cint%20%5Cfrac%7Bx%5E3%7D%7B%5Csqrt%7B9%2Bx%5E2%7D%7D%20%5C%2C%20dx%20%3D%209%20%5Cleft%28%5Cfrac%7B%5Cleft%28%5Csqrt%7B9%2Bx%5E2%7D%5Cright%29%5E3%7D%7B27%7D%20-%20%5Csqrt%7B9%2Bx%5E2%7D%5Cright%29%20%2B%20C)
![\displaystyle \int \frac{x^3}{\sqrt{9+x^2}} \, dx = \boxed{\frac13 \sqrt{9+x^2} (x^2 - 18) + C}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cint%20%5Cfrac%7Bx%5E3%7D%7B%5Csqrt%7B9%2Bx%5E2%7D%7D%20%5C%2C%20dx%20%3D%20%5Cboxed%7B%5Cfrac13%20%5Csqrt%7B9%2Bx%5E2%7D%20%28x%5E2%20-%2018%29%20%2B%20C%7D)
2(b). For some constants a, b, c, and d, we have
![\dfrac1{x^2+x^4} = \dfrac1{x^2(1+x^2)} = \boxed{\dfrac ax + \dfrac b{x^2} + \dfrac{cx+d}{x^2+1}}](https://tex.z-dn.net/?f=%5Cdfrac1%7Bx%5E2%2Bx%5E4%7D%20%3D%20%5Cdfrac1%7Bx%5E2%281%2Bx%5E2%29%7D%20%3D%20%5Cboxed%7B%5Cdfrac%20ax%20%2B%20%5Cdfrac%20b%7Bx%5E2%7D%20%2B%20%5Cdfrac%7Bcx%2Bd%7D%7Bx%5E2%2B1%7D%7D)
3(a). For some constants a, b, and c,
![\dfrac{x^2+4}{x^3-3x^2+2x} = \dfrac{x^2+4}{x(x-1)(x-2)} = \boxed{\dfrac ax + \dfrac b{x-1} + \dfrac c{x-2}}](https://tex.z-dn.net/?f=%5Cdfrac%7Bx%5E2%2B4%7D%7Bx%5E3-3x%5E2%2B2x%7D%20%3D%20%5Cdfrac%7Bx%5E2%2B4%7D%7Bx%28x-1%29%28x-2%29%7D%20%3D%20%5Cboxed%7B%5Cdfrac%20ax%20%2B%20%5Cdfrac%20b%7Bx-1%7D%20%2B%20%5Cdfrac%20c%7Bx-2%7D%7D)
5(a). For some constants a-f,
![\dfrac{x^5+1}{(x^2-x)(x^4+2x^2+1)} = \dfrac{x^5+1}{x(x-1)(x+1)(x^2+1)^2} \\\\ = \dfrac{x^4 - x^3 + x^2 - x + 1}{x(x-1)(x^2+1)^2} = \boxed{\dfrac ax + \dfrac b{x-1} + \dfrac{cx+d}{x^2+1} + \dfrac{ex+f}{(x^2+1)^2}}](https://tex.z-dn.net/?f=%5Cdfrac%7Bx%5E5%2B1%7D%7B%28x%5E2-x%29%28x%5E4%2B2x%5E2%2B1%29%7D%20%3D%20%5Cdfrac%7Bx%5E5%2B1%7D%7Bx%28x-1%29%28x%2B1%29%28x%5E2%2B1%29%5E2%7D%20%5C%5C%5C%5C%20%3D%20%5Cdfrac%7Bx%5E4%20-%20x%5E3%20%2B%20x%5E2%20-%20x%20%2B%201%7D%7Bx%28x-1%29%28x%5E2%2B1%29%5E2%7D%20%3D%20%5Cboxed%7B%5Cdfrac%20ax%20%2B%20%5Cdfrac%20b%7Bx-1%7D%20%2B%20%5Cdfrac%7Bcx%2Bd%7D%7Bx%5E2%2B1%7D%20%2B%20%5Cdfrac%7Bex%2Bf%7D%7B%28x%5E2%2B1%29%5E2%7D%7D)
where we use the sum-of-5th-powers identity,
![a^5 + b^5 = (a+b) (a^4-a^3b+a^2b^2-ab^3+b^4)](https://tex.z-dn.net/?f=a%5E5%20%2B%20b%5E5%20%3D%20%28a%2Bb%29%20%28a%5E4-a%5E3b%2Ba%5E2b%5E2-ab%5E3%2Bb%5E4%29)